Modification of the optical and elastic properties of TlGaSe2 layered semiconductor produced by the memory effect - Cengiz, Asuman; Goren, Serdar; Sonmez, Ayse; Sale, Yasin; Okumus, Esra; Kirbas, Cafer; Chumakov, Yurii M. (Iop Publishing Ltd, 2023)
A comparative analysis of the temperature behaviors of optical and elastic properties of TlGaSe(2 )single crystals under a memory effect experimental condition are presented for the first time. A memory effect condition suggests that the sample is thermally annealed inside the incommensurate (INC) phase for a time interval the corresponding physical parameters is measured experimentally. From ultrasound velocity measurements, carried out before and after the thermal annealing process subjected to the sample, the noticeable changes in the temperature variation of the longitudinal ultrasonic wave velocity associated with the elastic constants C(33 )of TlGaSe2 due to the memory effect was detected. Our results reveal that thermal annealing performed at the INC - phase has some influence on the optical absorption of TlGaSe2 crystals in the visible spectral region. We assumed that thermal annealing within INC - phase is accompanied with the appearance, inside TlGaSe2 samples, a new quasiperiodic frozen structure formed from the intrinsic defects migrated into the lowest energy diffusion barriers of the INC - modulation wave. Such structural modulation is incommensurate with the underlying lattice of TlGaSe2 and can lead to changes in the electronic band structure and the optical bandgaps of TlGaSe2 .
Keywords: semiconductor; ferroelectric; incommensurate phase; the memory effect; optical 30 absorption spectra; longitudinal and transverse ultrasonic waves; vacancy type defects